ChemInform Abstract: 4‐Isocyanopermethylbutane‐1, 1, 3‐triol (IPB): A Convertible Isonitrile for Multicomponent Reactions. Issue 1 (3rd January 2013) - Neves Filho, Ricardo A. W.; Stark, Sebastian; Morejon, Micjel C.; Westermann, Bernhard; Wessjohann, Ludger A.
Abstract The title compound (I) is efficiently employed in Ugi, Smiles, and Passerini multicomponent reactions.